2014
DOI: 10.1111/bju.12800
|View full text |Cite
|
Sign up to set email alerts
|

Early urinary continence recovery after robot‐assisted radical prostatectomy in older Australian men

Abstract: ObjectiveTo compare the recovery of urinary continence (UC) after robot-assisted radical prostatectomy (RARP) in men aged ≥70 and <70 years at 1-year follow-up and to assess for preoperative predictors of UC recovery, as older, healthy men with localised prostate cancer are often denied curative surgical treatment on the grounds of worse UC recovery. Patients and methodsIn all, 262 patients with prostate cancer having undergone RARP between May 2008 and September 2012, under the care of two consultant urologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…43 Unlike reports in ORP in which older men are more likely to experience long-term postoperative incontinence, early data suggest similar rates of incontinence in older and younger men after RARP. 44 Kumar and colleagues 45 observed similar continence rates among patients aged 70 years or older (median age 72 years) and those aged 70 years or younger (median age 62 years) at 1 year after RARP (87.3% and 91.3%, P 5 .07). Similarly, incidence of biochemical recurrence at 3 and 5 years postoperatively was also observed to be similar, but differences in cancer-specific survival approached statistical significance at 5-year follow-up between patients aged 70 years or older and those aged 70 years or younger (biochemical recurrence: 81.1% and 91.1%, P 5 .83 and cancer-specific survival: 95.3% and 98.2%, P 5 .06, respectively).…”
Section: Prostatectomymentioning
confidence: 82%
“…43 Unlike reports in ORP in which older men are more likely to experience long-term postoperative incontinence, early data suggest similar rates of incontinence in older and younger men after RARP. 44 Kumar and colleagues 45 observed similar continence rates among patients aged 70 years or older (median age 72 years) and those aged 70 years or younger (median age 62 years) at 1 year after RARP (87.3% and 91.3%, P 5 .07). Similarly, incidence of biochemical recurrence at 3 and 5 years postoperatively was also observed to be similar, but differences in cancer-specific survival approached statistical significance at 5-year follow-up between patients aged 70 years or older and those aged 70 years or younger (biochemical recurrence: 81.1% and 91.1%, P 5 .83 and cancer-specific survival: 95.3% and 98.2%, P 5 .06, respectively).…”
Section: Prostatectomymentioning
confidence: 82%
“…A large Italian study demonstrated that early pelvic floor muscle training following RP both significantly improved time to continence recovery with 94.6% of the men who participated in pelvic floor re-training being continent at 6 months following surgery compared to 65% in the control group (8). Interestingly increasing age may delay recovery but overall results are similar (9). Finally laparoscopic versus open or robotic approach may ultimately also be similar although more data are required to demonstrate a superiority related to technique (10).…”
Section: Introductionmentioning
confidence: 80%
“…analysed complications post‐robotic‐assisted RP between men under 69 and over 70 years in 868 men, and they found overall post‐operative complication rate for over 70 at 15.4%. In addition, 12‐month post‐operative potency and continence rates have been reported to be 75% and 69–92%, respectively . Further studies of direct comparisons between these two techniques in this cohort would be advantageous, but current evidence is encouraging for the robotic technique as a viable alternative in elderly men requiring curative surgery.…”
Section: Discussionmentioning
confidence: 95%